(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The scientific article presents the problems of studying the stress-strain state of contour structures and shells of thin-walled spatial coatings due to their joint work. Factors of changing the design solutions of contour diaphragms (bars) are given to study their joint work with shells. The issue of ultimate stresses and deformations of concrete in the biaxial stress-strain state of thin-walled spatial coatings in their corner zones is also considered. The factors of joint work of contour structures and shells for scientific research are established.